Implementasi Pemasaran Digital dan Kualitas Produk dalam Menarik dan Menjangkau Konsumen - Yoga Sampurna; Halimah Zahrah (Indo Publishing, 2026)
The development of digital technology has encouraged business actors to adopt more adaptive marketing strategies in response to increasing market competition. Digital marketing has become an important tool for attracting and reaching consumers, while product quality remains a key factor in building consumer trust and loyalty. This study aims to analyze the implementation of digital marketing and product quality in attracting and reaching consumers. This research employs a qualitative approach with a descriptive method. The study was conducted in Jl. Raya Derwati, Rancasari District, Bandung City, West Java. Data were collected through in-depth interviews, observation, and documentation involving business actors and consumers selected using purposive sampling. Data analysis was carried out through data reduction, data presentation, and conclusion drawing, with data validity ensured through source and technique triangulation. The findings indicate that digital marketing plays a significant role in expanding consumer reach and increasing consumer interest, while product quality serves as a determining factor in consumer satisfaction and trust. The integration of effective digital marketing strategies with consistent product quality can enhance business competitiveness in the digital era.